Pengaruh Pemberian Kompos Pada Kelembapan Tanah - Lase, Elikana (Jurnal Ilmu Pertanian dan Perikanan, 2025)
The use of compost as organic material has been proven to have a positive effect on the physical properties of the soil, one of which is increasing soil moisture. This study aims to examine the effect of composting on soil moisture through a literature review approach. Data were obtained from various relevant scientific sources, such as research journals, scientific articles, and academic reports published between 2014 and 2024. The results of the study showed that compost from various sources, such as rice straw, gamal leaves, and banana stems, can increase the soil's capacity to store water. This is due to the organic matter content in compost which improves soil structure, increases aggregation, and enlarges soil micropores. Increased soil moisture due to composting also has an impact on plant growth, especially on dry or marginal land. The effectiveness of compost in maintaining soil moisture is influenced by several factors, such as soil type, dosage, type of compost material, and the level of maturity of the compost itself. Thus, compost plays an important role in water conservation and increasing agricultural productivity sustainably. This study recommends the need for further experimental research to directly test the effectiveness of various types of compost in different agro-climatic conditions.